EUS Morphology Is Reliable in Selecting Patients with Mucinous Pancreatic Cyst(s) Most Likely to Benefit from Surgical Resection - Siddharth Javia; Satish Munigala; Sushovan Guha; Banke Agarwal (Gastroenterology Research and Practice)
Background and Study Aims. Endoscopic ultrasound (EUS) surveillance of patients with mucinous pancreatic cysts relies on the assessment of morphologic features suggestive of malignant transformation. These criteria were derived from the evaluation of surgical pathology in patients with pancreatic cysts who underwent surgery. Reliability of these criteria when evaluated by EUS in identifying lesions which require surgery has still not been established. Patients and Methods. This retrospective cohort study included seventy-eight patients who underwent surgical resection of pancreatic cysts based on EUS-FNA (fine-needle aspiration) findings suggestive of mucinous pancreatic cysts with concern for malignancy. Results. Final surgical pathology diagnoses of patients were the following: adenocarcinoma (19), intraductal papillary mucinous neoplasm (IPMN) (39), mucinous cystic neoplasm (MCN) (13), serous cystadenoma (2), pseudocyst (3), mucinous solid-cystic lesion of indeterminate type (1), and mesenteric cyst (1). Cysts with focal wall thickening ≥ 3 mm (p=0.0008), dilation of pancreatic duct (PD) (p=0.0067), and cyst size ≥ 3 cm (p=0.016) had significantly higher risk of adenocarcinoma. None of the patients without any of these morphologic features had cancer. Conclusions. In patients with mucinous pancreatic cyst(s), focal wall thickening, cyst size ≥ 3 cm, and PD dilation as assessed by EUS can help identify advanced mucinous cysts which require surgery and should routinely be evaluated during EUS surveillance.